Application of Vacuum Techniques in Shell Moulds Produced by Additive Manufacturing - P. Rodríguez-González (Metals, 2020)
This research shows the feasibility of the additive manufacturing technique (AM), Binder Jetting (BJ), for the production of shell moulds, which are filled by vacuum suction in the field of aluminium parts production. In addition, this study compares the gravity pouring technique and highlights the advantages of using vacuum techniques in AM moulds. A numerical simulation was carried out to study the behaviour of the liquid metal inside the moulds and the cooling rate of parts was analysed. The results show that in the gravity-pouring mould, the velocity in the gate causes moderate turbulence with small waves. However, vacuum suction keeps the velocity constant by eliminating waves and the filling process is homogeneous. Regarding dimensional accuracy, the staircase effect on the surface of the 3D moulds was the most critical aspect. The vacuum provides very homogeneous values of roughness across the entire surface of the part. Similarly, 3D scanning of castings revealed more accurate dimensions thanks to the help of vacuum forces. Finally, the microstructure of the cross section of the moulded parts shows that the porosity decreases with the vacuum filled. In both cases, the origin of the pores corresponds to gas entrapment and shrinkage during the filling process, the binder vaporization and nucleation points creation, leading to pores by shrinkage, gas entrapment or a mixture of both. This is the first study that uses vacuum filling techniques in moulds created by BJ, demonstrating the feasibility and advantages of AM using vacuum techniques, as an alternative to traditional casting.